Looking for diagnostics parameters of bearings of the gas turbine engine LM 2500 on the basis of mechanical contaminations in the lubricating oil - Waldemar MIRONIUK (Transport Problems, 2009)
While operation a gas turbine engine more modest methods of research are brought into effect. But one of the basic methods to estimate the technical condition of gas turbine engines bearing is oil analysis. To estimate the technical condition of gas turbine engines bearing systems on the basis of oil research on, an x-ray method of radio-isotope fluorescence was used. This method has been also satisfactorily used in aircraft engine diagnosis.This paper presents the method of diagnosis bearings of marine gas turbines on the basis of studies of mechanical contamination in oil. Results of mechanical contamination research in oil vs time of engine work are presented. On the basis of experiments results the analytical function that makes calculating the future value of the process possible was chosen.